2016
DOI: 10.1093/jmicro/dfw037
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for the direct visualization of the membrane cytoskeleton in cryo-electron microscopy: a comparative study with freeze-etching electron microscopy

Abstract: An improved unroofing method consisting of tearing off the cell membrane using an adhesive electron microscopy (EM) grid instead of vitreous ice sectioning (cryo-sectioning) has enabled us to panoramically view the membrane cytoskeleton in its native state with extremely high contrast. Grids pre-treated with Alcian blue were placed on cells, and a portion of the dorsal plasma membrane was transferred onto the grid, which was then floated in buffer solution. These membrane fragments contained sufficient cytoske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Imaging of DC-SIGN clusters in cells expressing a fluorescent construct containing the MT-binding domain of ensconsin demonstrated that many cluster trajectories are coincident with MTs. Recent electron microscopy studies demonstrate that some MTs are present in close proximity to the plasma membrane ( 45 ). Moreover, the MT-depolymerizing drug nocodazole, but not latrunculin A, which disrupts F-actin, suppresses a fraction of clusters undergoing rapid, directed movement, further implicating MTs in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging of DC-SIGN clusters in cells expressing a fluorescent construct containing the MT-binding domain of ensconsin demonstrated that many cluster trajectories are coincident with MTs. Recent electron microscopy studies demonstrate that some MTs are present in close proximity to the plasma membrane ( 45 ). Moreover, the MT-depolymerizing drug nocodazole, but not latrunculin A, which disrupts F-actin, suppresses a fraction of clusters undergoing rapid, directed movement, further implicating MTs in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…46 Recent in vitro studies advanced our understanding of the architecture of the actin cytoskeleton. 47,48 However, advances in new super resolution microscopy techniques such as stimulated emission depletion or stochastic optical reconstruction microscopy now offer new avenues to fully understand the complexity, composition, and dynamics of the podocyte actin cytoskeleton in vivo. 49 Additional insights into the structural and functional relation of FPs have come to light through the study of dramatic changes in podocyte morphology which take place during glomerular development, where cuboidal nonfiltering podocytes differentiate into arborized octopus-like filtering cells 50 (Figure 1).…”
Section: Actin Cytoskeletonmentioning
confidence: 99%
“…Although the presently employed methods failed to reveal the total network of ER throughout the cell, they did provide structural evidence of the relationship between podosomes and smooth ER in the OC. Some types of the smooth ER network can be visualized reliably only by using quick freezing techniques (Kanaseki et al, 1998;Makihara et al, 2016). Previous studies by replica electron microscopy pointed out the presence of variable types of membrane components termed variously as ER (Aggeler, Takemura, & Werb, 1983;Makihara et al, 2016), membranous organelle (Isobe, Warner, & Lemanski, 1988), anastomotic membrane tubule (Heuser & Anderson, 1989), and putative membrane component (Svitkina, Verkhovsky, & Borisy, 1996).…”
Section: Structural Relationship Between the Podosomes And The Intrmentioning
confidence: 99%